Firms' ethics, consumer boycotts, and signalling - Amihai Glazer; Vesa Kanniainen; Panu Poutvaara (Institute for the Study of Labor (IZA), 2008)
This paper develops a theory of consumer boycotts. Some consumers care not only about the products they buy but also about whether the firm behaves ethically. Other consumers do not care about the behavior of the firm but yet may like to give the impression of being ethical consumers. Consequently, to affect a firm's ethical behavior, moral consumers refuse to buy from an unethical firm. Consumers who do not care about ethical behavior may join the boycott to (falsely) signal that they do care. In the firm's choice between ethical and unethical behavior, the optimality of mixed and pure strategies depends on the cost of behaving ethically. In particular, when the cost is (relatively) low, ethical behavior arises from a prisoners' dilemma as the firm's optimal strategy.
urn:nbn:de:101:1-20080527186
Keywords: M14; 650; Firm's ethical code; consumer morality; boycotts; Unternehmensethik; Verbraucherboykott; Signalling; Strategische Unternehmensplanung; Gefangenendilemma